Mechanism of COVID-19 Causing ARDS: Exploring the Possibility of Preventing and Treating SARS-CoV-2 - Zheng, Jiajing; Miao, Jiameng; Guo, Rui; Guo, Jinhe; Fan, Zheng; Kong, Xianbin; Gao, Rui; Yang, Long (Frontiers in Cellular and Infection Microbiology, 2022)
Novel coronavirus pneumonia (COVID-19) is spreading worldwide, causing great harm and stress to humans. Since patients with novel coronavirus (SARS-CoV-2) have a high probability of developing acute respiratory distress syndrome (ARDS) in severe cases, the pathways through which SARS-CoV-2 causes lung injury have become a major concern in the scientific field. In this paper, we investigate the relationship between SARS-CoV-2 and lung injury and explore the possible mechanisms of COVID-19 in ARDS from the perspectives of angiotensin-converting enzyme 2 protein, cytokine storm, activation of the immune response, triggering of Fas/FasL signaling pathway to promote apoptosis, JAK/STAT pathway, NF-κB pathway, type I interferon, vitamin D, and explore the possibility of prevention and treatment of COVID-19. To explore the possibility of SARS-CoV-2, and to provide new ideas to stop the development of ARDS in COVID-19 patients.